Common Polymorphism’s Analysis of Thiopurine S-Methyltransferase (TPMT) in Iranian Population - Mehdi Azad; Saeid Kaviani; Masoud Soleimani; Mehrdad Noruzinia; Abbas Hajfathali (Cell Journal, 2009)
Objective: Thiopurine S-methyltransferase (TPMT) catalyses the S-methylation of thiopurinedrugs. Low activity phenotypes are correlated with several mutations in the TPMTgene and adverse drug reactions. The molecular basis for dissimilar enzymatic activityof TPMT has been established in Caucasians, African-Americans and Southwest Asians,but it remains to be elucidated in Iranian population. Until present, no study on Iranianpopulation has been performed on the known alleles of TPMT. The aim of this study wasto investigate the frequencies of four of the most common variants of this gene.Materials and Methods: This study was conducted during 2007 at the Department of Hematology,Tarbiat Modares University, Tehran, Iran. Using PCR-RFLP and allele specificPCR techniques, allelic variants of the TPMT gene TPMT*2(G238C), TPMT*3B (G460A),TPMT*3C (A719G) and TPMT*3A (G460A and A719G) were genotyped in a normal populationof 127 Iranians.Results: In this study TPMT*2 showed a prevalence of 7.08%. TPMT*3C and *3A werefound in 2.47% and 2.18% of the samples, respectively. TPMT*3B variant was not detectedin Iranian subjects. 112 out of 127 participants showed homozygote wild type allele.Conclusion: This study is the first to analyze TPMT allele frequencies in a sample ofIranian population and indicates that TPMT*2 is the most common allele (7.08%) in thispopulation. These results can help to organize national pretreatment strategies in patientswith acute lympho blastic leukemia (ALL) or other diseases requiring thiopurine medicationin their standard therapy.